2021
DOI: 10.1186/s12905-021-01544-6
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual characteristics, menstrual anxiety and school attendance among adolescents in Uganda: a longitudinal study

Abstract: Background Qualitative data show negative impacts of menstruation on health and education in many settings, but there are few longitudinal quantitative studies of the impact of menstruation. We analyse associations with menstrual anxiety and school attendance in a study of Ugandan secondary school students. Methods Data were from a longitudinal pilot study of a menstrual health intervention (MENISCUS), conducted in two secondary schools in Entebbe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
1
8
0
2
Order By: Relevance
“…This study found that younger women were more likely to have unmet need for MHM compared to older women aged 35 and above. This nding is attributable to the fact that younger women are more likely to be exposed to MHM barriers in school (29)(30)(31), work (23) and other physical activities like sporting(16); and are highly likely to be impacted by menstrual challenges (32). Younger women therefore present as the age-group with a greater need for adequate MHM, which explains why most previous studies have focused on adolescent girls and school-age women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that younger women were more likely to have unmet need for MHM compared to older women aged 35 and above. This nding is attributable to the fact that younger women are more likely to be exposed to MHM barriers in school (29)(30)(31), work (23) and other physical activities like sporting(16); and are highly likely to be impacted by menstrual challenges (32). Younger women therefore present as the age-group with a greater need for adequate MHM, which explains why most previous studies have focused on adolescent girls and school-age women.…”
Section: Discussionmentioning
confidence: 99%
“…The study included 4427 women in Kenya, 4406 in Ethiopia, 2667 in Uganda, 1976 in Burkina Faso, 1766 in Niger and 2806 in Ghana. Most of the participants in the six countries were middle aged (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), were married or cohabiting and had never given birth(parity). While most of the countries had higher proportion of urban residents, Kenya and Uganda had higher proportions of rural residents.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…A study conducted by Mohamadirizi and Kordi showed that a high percentage of students suffer from psychological disorders; it also indicated a significant link between menstruation signs and anxiety, depression, and stress [ 25 ]. A longitudinal study undertaken in Uganda among adolescents regarding menstrual characteristics and menstrual anxiety similarly revealed that menstruation caused substantial anxiety [ 26 ]. It also showed that menstrual problems had a clinically and statistically significant association with depression among adolescent girls aged 9-11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in a systematic review and qualitative meta-synthesis of women’s and girls’ experiences of menstruation, where girls perceived menarche as something to be feared [ 1 ]. This may lead to anxiety, depression and a lack of preparedness on how to handle menstruation [ 30 , 31 ]. Additionally, our findings showed the limited knowledge and the unmet need for engaging boys and male teachers, who have the potential to support females in MH.…”
Section: Discussionmentioning
confidence: 99%